The Effect of Blue Light Filter Lens Glasses on The Occurrence of Asthenopia Symptoms in Visual Display Terminal Users - Mustikaningrum, Arif Hening; Soemarko, Dewi Sumaryani; Widyahening, Indah Suci (UI Scholars Hub, 2025)
The widespread use of Visual Display Terminals (VDTs) is associated with visual and musculoskeletal complaints, particularly Asthenopia, which may reduce productivity. A 32-year-old female financial worker presented with eye discomfort, including sore eyes, blurred vision, dizziness, and twitching on her left temple, particularly during extended computer use. The symptoms were relieved with rest. Most VDTs now use Light Emitting Diodes, which emit more blue light than LCDs and may cause eye fatigue and disrupt sleep. Currently, blue light filter lenses are available in the market, however, further study of existing scientific publications is necessary to ensure the effectiveness of blue light filter lenses, which are claimed to reduce asthenopia symptoms. This Evidence-based case report (EBCR) questions whether blue-light filter lens glasses alleviate symptoms of Asthenopia in workers A literature search in PubMed, Cochrane, and Embase identified Systematic Reviews, Meta-Analyses, and Randomized Controlled Trials (RCTs) evaluating blue light filter lenses in VDT users. These studies assessed objective measures (Critical Flicker Fusion Frequency—CFF) and subjective symptoms via questionnaires. The research papers were critically reviewed using the Oxford CEBM criteria for therapy (intervention) studies. Four Randomized Controlled Trial research articles met our criteria. However, the results did not provide conclusive evidence. There was no significant improvement in Critical Fusion Frequency (CFF), nor a reduction in subjective symptoms based on questionnaires. All studies varied in methodology, filter specifications, outcome tools, and subject characteristics. Therefore, blue light filter lenses cannot yet be clinically recommended for reducing asthenopia symptoms in VDT users. Further research is needed with a stronger design, larger sample size, and clearer standards and operational definitions.